Dose rates and specific activities of Li2CO3 pellets and diamond detectors irradiated during TT and DTE2 campaigns at JET. (December 2021) - Slavickas, Andrius; Stankunas, Gediminas; Tidikas, Andrius; Breidokaite, Simona; ,
Abstract: TT and DTE2 campaigns at JET are expected to produce large 14 MeV neutron fluxes that will enable the expansion of activation detection ranges. The calculation results of the activation and dose rates induced in Li2 CO3 pellets and diamond detector materials are presented in this research. The MCNP code was used in order to produce corresponding neutron flux densities and spectra. The FISPACT code with the EAF-2010 library was used to estimate the activation and dose rates. Highlights: TT and the DTE2 campaigns are expected to produce large 14 MeV neutron fluxes. The detailed irradiation scenarios for a day to day basis were considered for the analysis. Neutron-induced activities on the diamond detectors and LI pellets were calculated. Li pellets classify as LLWR in UK as long-lived H-3 dominates in pellets activity.